Cyrus Robinson Miller papers - Miller, Cyrus Robinson, 1874-1947.
Midshipman's logs (1897-1898) documenting activities of the U.S. battleship Oregon during the Spanish-American War and the armored cruiser Buffalo; radio logs of the protected cruiser Cleveland which led merchant convoys in the Atlantic Ocean during World War I; and a ditty about life aboard the troop ship Von Steuben.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: United States. -- Navy -- Sea life; Buffalo (Armored cruiser); Cleveland (Protected cruiser); Oregon (Battleship); Von Steuben (Troop ship); Merchant marine; Naval convoys -- Atlantic Ocean; Sea songs; Spanish-American War, 1898 -- Naval operations, American; World War, 1914-1918 -- Naval operations, American; Naval officers